Predictive value of the specific radiographic signs at panoramic radiography indicating possible close relationship of posterior teeth and surrounding anatomical structures: A CBCT study - Djordjević, Aleksandar; Todić, Jelena; Arsić, Zoran; Ilić, Aleksandra; Jovanović, Radovan; Vlahović, Zoran (Vojnosanitetski pregled, 2021)
Background/Aim. In planning the extraction of posterior teeth, it is necessary to determine their position and correlation with the surrounding anatomical structures. The aim of this study was to perform Cone Beam Computed Tomography (CBCT) analysis in order to evaluate the predictive value of specific orthopantomography (OPT) radiographic signs in determining the proximity of posterior upper teeth to the maxillary sinus and lower teeth to the mandibular canal. Methods. In a prospective study, 460 cases out of 423 patients were analyzed. Seven OPT radiographic signs were assessed to determine the correlation of the third molars to the mandibular canal, while five radiographic signs were followed to determine the correlation of the maxillary sinus floor to the upper posterior teeth. For each OPT radiographic sign, a precise analysis of the axial slices of the CBCT was performed. Results. Interruption of the white line is a radiographic sign showing statistically significant interruption of the integrity of the mandibular canal on the CBCT axial slices (p = 0.002). Also, diversion of the inferior alveolar canal at the axial sections showed statistically significant interruption of the continuity of the mandibular canal (p = 0.003). A radiographic sign, Darkening of the root, showed superimposition of the anatomical structures, a close relationship with the tooth but often with preserved mandibular canal integrity (p < 0.001). Absence of lamina dura, interruption of the maxillary sinus floor's cortex, and projection of the root apices in the sinus cavity were radiographic signs that were statistically the most commonly associated with interruption of maxillary sinus integrity on CBCT axial slices (p < 0.001). Conclusion. The results of our study indicate that the presence of certain radiographic signs on the OPT may have predictive significance. The exact relationship between anatomical structures and posterior teeth cannot be accurately estimated on OPT. The precise position of the molars and correlation to the mandibular canal and the maxillary sinus can be accurately determined by CBCT imaging.
Keywords: radiography, panoramic; cone beam computed tomography; mandible; maxillary sinus